Antioxidant activity and total phenolic content of essential oils and extracts of sweet basil (Ocimum basilicum L.) plants - Adel F. Ahmed; Fatma A.K. Attia; Zhenhua Liu; Changqin Li; Jinfeng Wei; Wenyi Kang (Food Science and Human Wellness)
The present study was conducted to evaluate the chemical composition and antioxidant activity of the essential oils and ethanol extracts of Ocimum basilicum L. obtained from Assiut, Minia and BeniSuef of Egypt. The major constituents of sweet basil essential oils from three locations were linalool, estragole, methyl cinnamate, bicyclosesquiphellandrene, eucalyptol, α-bergamotene, eugenol, γ-cadinene and germacrene D by the method of GC–MS. The relative concentration of these compounds varies. The basil extracts contained appreciable levels of total phenolic contents and exhibited good DPPH radical scavenging capacity higher than that of essential oils. The highest TPC (82.45 mg PE/g) and maximum radical scavenging activity with IC50 value (1.29 mg/mL) was obtained from Minia basil extract. High correlation between antioxidant activity and total phenolic contents of basil extracts was observed. High variation in free radical scavenging activity of essential oils was found. The essential oil from Minia basil showed high activity in DPPH radical scavenging with IC50 (11.23 mg/mL) and contained the highest content of phenolic (41.3 mg PE/g). On contrary, low correlation between antioxidant activity and total phenolic contents of basil essential oils from different locations. The results of the present investigation demonstrated significant variations in the antioxidant activities of sweet basil essential oils and extracts from Egypt. Keywords: Ocimum basilicum, Essential oils, GC–MS, Total phenolic contents, Antioxidant activities